1999
DOI: 10.1002/(sici)1521-3927(19991201)20:12<637::aid-marc637>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Living polymerization of propylene and 1-hexene using bis-Cp type metallocene catalysts

Abstract: SUMMARY: To check the possibility of living polymerization with a biscyclopentadienyl metallocene, propylene polymerization was conducted by Cp 2 ZrMe 2 at -78 8C or Cp 2 HfMe 2 at -50 8C using B(C 6 F 5 ) 3 and AlOct 3 as a cocatalyst. The polymer yield increased linearly with polymerization time. The polypropylene obtained showed narrow molecular weight distribution (M -w /M -n 1.04 -1.15). In addition, the number-average molecular weight increased in proportion to the polymerization time. It was, thus, foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 7 publications
(12 reference statements)
0
29
0
1
Order By: Relevance
“…[84] Die Arbeitsgruppen um Shiono und Fukui untersuchten daher Olefinpolymerisationen mit Metallocen-Katalysatoren oder solchen mit gespanntem Ligandensystem bei sehr tiefen Temperaturen. [87] Die Zahl der Polymerketten blieb im Verlauf der Reaktion konstant, d. h., Ketten¸bertragungen traten bei dieser tiefen Temperatur nicht auf. [85] Der Titan-Katalysator 22 lieferte nach Aktivierung mit B(C 6 F 5 ) 3 [86] Fukui et al fanden, dass der einfache B(C 6 F 5 ) 3 -aktivierte Bis(Cp)-Katalysator 23 a Propen bei À 78 8C in Gegenwart von Trioctylaluminium als Cokatalysator lebend polymerisiert.…”
Section: Metallocenkomplexeunclassified
“…[84] Die Arbeitsgruppen um Shiono und Fukui untersuchten daher Olefinpolymerisationen mit Metallocen-Katalysatoren oder solchen mit gespanntem Ligandensystem bei sehr tiefen Temperaturen. [87] Die Zahl der Polymerketten blieb im Verlauf der Reaktion konstant, d. h., Ketten¸bertragungen traten bei dieser tiefen Temperatur nicht auf. [85] Der Titan-Katalysator 22 lieferte nach Aktivierung mit B(C 6 F 5 ) 3 [86] Fukui et al fanden, dass der einfache B(C 6 F 5 ) 3 -aktivierte Bis(Cp)-Katalysator 23 a Propen bei À 78 8C in Gegenwart von Trioctylaluminium als Cokatalysator lebend polymerisiert.…”
Section: Metallocenkomplexeunclassified
“…The developmental activities of well‐defined transition metal catalysts capable of initiating stereospecific living propylene polymerization have been intense in the past three decades, because these catalysts may provide potentially high‐performance polymers such as monodisperse polypropylenes (PPs) with high melting temperatures ( T m s) and block copolymers containing high T m segment. Besides numerous catalysts capable of highly stereospecific polymerization of propylene,1–17 recent progress in the rational design of well‐defined catalysts for olefin polymerization has resulted in the discovery of a growing number of catalysts for living propylene polymerization 18–52. For example, biscyclopentadienyl metallocene,18 diamine bisphenolate zirconium complexes,19, 20 fluorinated bis(phenoxyketimine)titanium complexes,21–23 α‐diimine Ni(II)24 complexes, and monocyclopentadienyl zirconiumn complexes25 are able to catalyze propylene polymerization in a living manner.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous communication [6] we could demonstrated that simple metallocene systems such as the Cp 2 ZrMe 2 /B(C 6 F 5 ) 3 system had the potential for a living polymerization catalyst for propylene at -78 8C. More recently, we also confirmed that the living like polymerization of propylene took place with mixed metallocene system [for example, Cp 2 ZrMe 2 /B(C 6 F 5 ) 3 /Cp*TiCl 3 / AlOct 3 ] even at -50 8C.…”
Section: Introductionmentioning
confidence: 90%